Problem-Solving Skills of Seventh-Grade Students in Ratio Topic - Khoerunnisa, Hana Afiana; Aripin, Usman; Sabandar, Jozua; Hanifah, Nida Fathiya (Edumatika, 2023)
The proficiency of students in mastering mathematical problem-solving skills stands as a pivotal criterion for the success of mathematics learning. This research aims to assess and portray the level of students' mastery of mathematical problem-solving skills, particularly within the context of the ratio topic. Employing a descriptive qualitative research design, the study involves 10 seventh-grade students from a junior high school in Cimahi, West Java, Indonesia. These students have diverse initial abilities, spanning low, medium, and high levels, as recommended by their mathematics teacher. Data collection is executed through tests encompassing five indicators of mathematical problem-solving skills outlined by the National Council of Teachers of Mathematics (NCTM). The students' answer sheets are meticulously examined to ascertain and evaluate the students' proficiency in mathematical problem-solving skills, specifically pertaining to the ratio topic. The research findings indicate that the seventh-grade students' mathematical problem-solving skills in the ratio topic are deemed quite proficient.